SOSIALISASI RANCANGAN PEMBANGUNAN NAGARI SUMANIAK KECAMATAN SALIMPAUNG KABUPATEN TANAH DATAR YANG RESPONSIF TERHADAP DAMPAK PANDEMI COVID-19 - Ade Suzana Eka Putri; Jendrius Jendrius; Masrizal Masrizal; Jenita Sari (BULETIN ILMIAH NAGARI MEMBANGUN, 2021)
The Covid-19 pandemic has had a comprehensive impact on all aspects of people's lives. The government has launched the Disaster Resilient Village program 2014 in empowering rural communities to face disasters. When the Covid-19 pandemic struck in West Sumatra, this program was echoed again in the form of the Nagari Tageh Program. However, the government and the Nagari community still need strengthening in planning and implementing this program. This activity aims to assist the community and the Sumaniak Nagari Government in preparing a Nagari development plan that is responsive to the impact of the Covid-19 pandemic through strengthening community empowerment. This activity was carried out in 2020 with the stages of identifying problems and priority needs of the Nagari community in reducing the impact of the Covid-19 pandemic, identifying programs and activities to resolve these problems, and discussing program financing through the Nagari government budget. This activity has resulted in programs and activities that have been agreed by the community and the Nagari government to be implemented in 2021. The resulting development plan reflects a development plan that is responsive to community problems and needs and is participatory because it involves the community in its preparation. Through partnership activities with Unand, the team will become Nagari partners starting from the planning, implementation, monitoring, and evaluation stages of the Nagari Tageh development program so that Nagari Sumaniak is ready to face pandemics and other disasters in the future and become an Independent Nagari in all aspects of development.